PENINGKATAN KECEPATAN EFEKTIF MEMBACA TULISAN BRAILLE DENGAN TEKNIK DUA TANGAN BAGI TUNANETRA KELAS V SLB NEGERI 2 PADANG - Jumaidi .; Atmazaki .; Harris Effendi Thahar (Bahasa, Sastra, dan Pembelajaran, 2013)
Abstract: This research is a classroom action research the purpose of increase the effective speed of reading braille for blind students a basic class V SLB Negeri 2 Padang by two hands technique. These research held in six times meeting by reseach design: 1) planning, 2) action, 3) observation, and 4) reflection. Research subjects are all three blind students in class V SLB Negeri 2 Padang. The research result is marked by the improvement of student effective speed reading. Thereby, the two hands technique should be applied in learning process of blind students in SLB Negeri 2 Padang. Kata Kunci: Kecepatan Efektif Membaca, Tulisan Braille, Teknik Dua Tangan,Tunanetra